Practicing Culturally Competent Therapeutic Jurisprudence: A Collaboration Between Social Work and Law - Carolyn Copps Hartley; Carrie J. Petrucci (Washington University Journal of Law & Policy, 2004)
The Essay will be presented in two parts. Part I lays the theoretical and empirical foundation for the need for an emphasis on lawyers’ cultural competence. Part II then details the substantive content of a culturally competent approach to lawyering. In Part I.A, we define Therapeutic Justice (“TJ”) and discuss some of its current applications. In Part I.B, we identify the commonalities between TJ and the generalist social work model. In Part I.C, we discuss the current thinking and debates on racial and ethnic disparities and discrimination in the criminal justice system from a macro social work perspective. Part I.D describes a TJ approach to lawyering that addresses how TJ might be used to uncover key aspects of racial and ethnic disparities in the legal process. Part I.E presents a discussion of the empirical research that supports the important emphasis on “relationship” in the lawyer-client relationship while arguing that specific attention to racial and ethnic competency is notably missing. In Part II.A, we provide a discussion of the role of race in the lawyer-client relationship using racial identity development theory. Finally, in Part II.B, we present a cultural competency education model that integrates existing approaches in social work and law, and advocates a process that includes recommendations for: institutional change; infusion of diversity content throughout law school curriculum; an exploration of issues of power and oppression; an exploration and challenging of one’s own racial beliefs and biases; and a skill-building component.
Keywords: Therapeutic jurisprudence; Social workers; Multidisciplinary practices; Multiculturalism; Criminal justice administration